2011
DOI: 10.3174/ajnr.a2381
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Integrated [18F] Fluorodeoxyglucose Positron-Emission Tomography/CT in Identifying Vulnerable Carotid Plaques

Abstract: BACKGROUND AND PURPOSE:There is a need for improved risk stratification of patients with TIA/ stroke and carotid atherosclerosis. The purpose of this study was to prospectively investigate the potential of integrated 18 F-FDG PET/MDCT in identifying vulnerable carotid plaques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
33
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 19 publications
4
33
0
3
Order By: Relevance
“…Our correlation coefficient for blood background of 0.75 inevitably increases the inter-observer variability of all background-corrected values. Other 18 F-FDG uptake reproducibility studies in localized carotid artery plaques have reported moderate (background corrected) 28 to excellent (with and without background correction) 22,29 inter-observer agreement. The slightly inferior inter-observer agreement for background-corrected values found in our study could be related to differences in the placement of the ROI in the jugular vein as the diameter of the jugular vein often was small, making the measurement susceptible to image noise.…”
Section: Discussionmentioning
confidence: 99%
“…Our correlation coefficient for blood background of 0.75 inevitably increases the inter-observer variability of all background-corrected values. Other 18 F-FDG uptake reproducibility studies in localized carotid artery plaques have reported moderate (background corrected) 28 to excellent (with and without background correction) 22,29 inter-observer agreement. The slightly inferior inter-observer agreement for background-corrected values found in our study could be related to differences in the placement of the ROI in the jugular vein as the diameter of the jugular vein often was small, making the measurement susceptible to image noise.…”
Section: Discussionmentioning
confidence: 99%
“…53,58,66 FDG imaging of carotid plaques shows the most promise when used as an adjunct to other imaging modalities, especially MRI. A number of investigators have examined the value of the combination of FDG-PET to detect active inflammation and MRI to identify worrisome morphological features for the optimization of risk stratification.…”
mentioning
confidence: 99%
“…34 Additionally, high FdG uptake is supposed to be detectable for around 1 month after symptoms, which is much longer than presence of MES. 30,35 Inflammation was predominant in the soft component of the plaque compared with the calcified one, emphasizing thereby the importance of measuring separately uptake within this part of the plaque. This finding was in agreement with an earlier study published by Rudd, which showed among 41 patients that calcification and inflammation rarely overlapped within arteries.…”
Section: Discussionmentioning
confidence: 99%